Impact Of Job Satisfaction On Organizational Commitment In Malaysian Organizations - Raghimi, Morteza (2010)
This study investigate the relationship between job satisfaction and organizational commitment in Multimedia University and Limkokwing University in Malaysia. As a result, in this study an attempt will be made to determine the impact of three faces of job satisfaction such as satisfaction with pay, promotion, and with co-worker on organizational commitment of Malaysian organization. The study also looked at how different measurement items of each faces of job satisfaction can predict each item of organizational commitment.